2018
DOI: 10.1128/aac.01675-17
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Compounds Are Bactericidal against Streptococcus mutans and Target the Bacitracin-Associated Efflux System

Abstract: Vitamin D analogs were identified as compounds that induced lysis of planktonic cultures of in a high-throughput screen of FDA-approved drugs. Previous studies have demonstrated that certain derivatives of vitamin D possess lytic activity against other bacteria, though the mechanism has not yet been established. Through the use of a combinatorial approach, the vitamin D derivative doxercalciferol was shown to act synergistically with bacitracin, a polypeptide-type drug that is known to interfere with cell wall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 76 publications
1
37
0
Order By: Relevance
“…The benefit of vitamin D in mineral metabolism and skeletal health is well-documented in the literature. In the endothelium, vitamin D modulates macrophage and T lymphocyte activity, and it exerts anti-inflammatory and antibacterial activities [126,127]. Vitamin D supplements show extensive benefits if the population has vitamin D deficiency [128][129][130][131][132].…”
Section: Vitamin D Supplement Is Beneficial In Ecs and Adipose Tissuementioning
confidence: 99%
“…The benefit of vitamin D in mineral metabolism and skeletal health is well-documented in the literature. In the endothelium, vitamin D modulates macrophage and T lymphocyte activity, and it exerts anti-inflammatory and antibacterial activities [126,127]. Vitamin D supplements show extensive benefits if the population has vitamin D deficiency [128][129][130][131][132].…”
Section: Vitamin D Supplement Is Beneficial In Ecs and Adipose Tissuementioning
confidence: 99%
“…In addition to assigning new activities to previously characterized compounds, compound libraries are also an ideal source of adjuvants, molecules that have little to no antibiotic activity alone but can be used in combination with other drugs to enhance antimicrobial activity and, in some cases, circumvent resistance mechanisms (26)(27)(28). For example, we found that the vitamin D derivative doxercalciferol acts synergistically with bacitracin through a mechanism involving the S. mutans bacitracin resistance transporter, MBR (29).…”
mentioning
confidence: 95%
“…The MIC for both vitamin C and gentamicin was measured using the same strains under the same conditions. FICI was interpreted according to standard de nitions, wherein a FICI of ≤ 0.5 was determined as a synergistic effect, a FICI of > 4.0 was determined as an antagonistic effect, and a FICI between 0.51 and 3.99 was determined as no interaction [39,40]. Line graph showing the relationship between absorbance at 560 nm and increasing vitamin C concentrations in the bio lm and growth assays.…”
Section: Kinetic Studymentioning
confidence: 99%